Polymerization of Acrylamide with Ceric Ion-Alanin Redox System: A Kinetic Study - Uduman Mohideen, A.M.; Alhaji, N.M.I.; Mohamed Farook, N.A. (Asian Journal of Chemistry, 2016)
The polymerization of acrylamide (AM) in aqueous sulphuric acid medium initiated with ceric ammonium sulphate-alanine redox system was investigated in the temperature range 30–50°C. The rate of polymerization (Rp) and the rate of cerium(IV) disappearance were measured. The influence of varying [acrylamide], [alanine] and [Ce(IV)] and the effects of organic solvents on the rate of polymerization were examined. The temperature depencence of the rate was studied and the activation parameters were calculated using Arrhenius and Erying plots. The initiation was caused by the free radical generated by the decomposition of the complex formed between Ce(IV) and alanine (AL). The chain termination step of polymerization reaction occurred by the mutual interaction of free radicals.